Implementasi Perubahan Peraturan mengenai Pembebasan Bea Masuk dan Pajak Impor pada Usaha Mikro Kecil dan Menengah - Lestari, Nanik; Hati, Shinta Wahyu; Bakhroni, Fery Yudha; Hadyjah, Besse (Studi Akuntansi dan Keuangan Indonesia, 2023)
The purpose of this research is to give the empirical evidence regarding the impact of the implementation of PMK Number 199 / PMK.010 / 2019 on MSMEs in Batam. The data used in this study are primary data. The data collection method utilizes a questionnaire via google form which is distributed in the WAG community and existing social media. The sample was 122 respondents who were MSME actors in Batam. The research findings indicate that the majority of SMEs are not aware of the contents and objectives of the regulations, have not received sufficient or effective socialization, are not aware of the mechanisms for deduction, payment, and reporting, do not know the amount of the tariffs to be paid, and this has resulted in a decrease in their business revenue and income.